Penatalaksanaan Fisioterapi Kontrol Postural pada Kasus Global Delay Development di School and Therapy Talitakum Semarang - Khairunnisa, Fatimah As-Syifa; Amanda, Tasya Ghea (Universitas Muhammadiyah Surakarta, 2023)
Introduction: Pregnancy-related Pelvic Girdle Pain (PGPP) is the most common condition during pregnancy that affects the quality of life, and a previous study has found that between 17% to 64.7% of pregnant women reported PPGP worldwide. The physiotherapy management of PPGP has varieties among countries, especially in the low- and middle-income countries (LMICs) group setting which are dependent on their country’s situations. The topics that need to discover more in the LMICs were the vulnerable maternal and neonatal morbidity and mortality risk factors. This could be the inadequate health service quality, lack of information, limited coverage, and low quality of antenatal care. Case Presentation: A literature review from five databases (PubMed, Pedro, Science Direct, Cochrane, and Web of Science). A mix of keywords has been used in the search or Medical Subject Heading (MESH) terms related to